Preparation, biological characterization and preliminary human imaging studies of 68Ga-DOTA-IBA - Wang, Yingwei; Wang, Qixin; Chen, Zan; Yang, Jian; Liu, Hanxiang; Peng, Dengsai; Lei, Lei; Liu, Lin; Wang, Li; Xing, Naiguo; Qiu, Lin; Feng, Yue; et al. (Frontiers in Oncology, 2022)
Purpose In this study, DOTA-IBA was radiolabeled with 68Ga and we determined the optimum labelling conditions and assessed the biological properties of 68Ga-DOTA-IBA. We investigated the biodistribution of 68Ga-DOTA-IBA in normal animals and undertook PET/CT imaging in humans. Finally, we explored the feasibility 68Ga-DOTA-IBA as a bone imaging agent and demonstrated its potential for the therapeutic release of 177Lu/225Ac-DOTA-IBA. Methods The controlled variables method was used to assess the impact of variables on the radiochemical purity of 68Ga-DOTA-IBA. The biological properties of 68Ga-DOTA-IBA were investigated.68Ga-DOTA-IBA micro-PET/CT imaging was performed on animals. Volunteers were recruited for 68Ga-DOTA-IBA imaging and data were compared to 99mTc-MDP imaging studies to calculate the target to non-target ratio (T/NT) of the lesions. Results The prepared 68Ga-DOTA-IBA had a radiochemical purity of >97% and demonstrated good biological properties with a good safety profile in normal mice. PET/CT imaging of the animals showed rapid blood clearance with high contrast between the bone and stroma. Human imaging showed that 68Ga-DOTA-IBA could detect more lesions compared to 99mTc-MDP and had a higher targeted to untargeted ratio. Conclusions 68Ga-DOTA-IBA is an osteophilic radiopharmaceutical that can be synthesized using a simple labelling method. 68Ga-DOTA-IBA has high radiochemical purity and is stable in vitro stability. It is rapidly cleared from the blood, has low toxicity and has strong targeting to the bone with long retention times. We also found that it is rapidly cleared in non-target tissues and has high contrast on whole-body bone imaging. 68Ga-DOTA-IBA PET/CT has potential as a novel bone imaging bone modality in patients with metastatic disease.